Grammatical sensitivity: a correlational-explanatory study on brain dominance and Efl training to improve gains - Piraud, Muriel Oyarce (Colombian Applied Linguistics Journal, 2008)
This article provides a report on a finished piece of research. The study is divided into two stages. Firstly, the brain dominance and grammatical sensitivity of Pedagogy and Medical students in a Chilean university were measured. The correlation of both variables shows that Medical students are better at grammatical sensitivity than Pedagogy students and that left-brain dominance involves higher levels of grammatical sensitivity than right-brain dominance. The instruments used in this stage were: 1) a grammatical sensitivity pre- test (used to assess the students’ levels in this variable), 2) a brain dominance instrument (used to determine the cerebral preferences of the students) and 3) an abstract reasoning test (which measures a person’s ability to identify non numerical or verbal patterns). In the second stage, Pedagogy students underwent a five-session training aimed at improving their grammatical sensitivity. After the training was over, we administered a grammatical sensitivity post- test whose results were compared with the ones in the pre-test; the purpose was to determine if the training could improve the students’ performance in this variable. It was concluded that the training was successful since their grammatical sensitivity improved in 20%. In addition, most students with high attendance to the training (over 80%) improved their grammatical sensitivity after attending it.